LEGAL AND ILLEGAL APPROACH IN DETERMINING TERMINOLOGICAL EQUIVALENTS IN THE PROCESS OF TRANSLATION ON THE EXAMPLE OF SELECTED TERMINOLOGY FROM THE TRANSLATION OF THE CANTON OF ZURICH - Iluk, Łukasz (Comparative Legilinguistics, 2020)
Authors of translations of legal codes do not usually inform about their approach to solving translational problems. One of the reasons is the firm belief in the need for a faithful and thus literal translation of the output text. This unlawful approach creates a field for unfounded creation of so-called Equivalent terminology. Consequently, translations contain expressions whose meanings in the target language are incomprehensible or cannot be determined by reference to the doctrine or case-law. A legal approach based on subject knowledge and a precise methodology for determining interlingua equivalents eliminates the problems arising from a non-lawful approach . In the analytical part of the article it is presented the methodology of the legal approach to solving translational problems and the method of its practical application.